Doing developmental research a practical guide - Striano, Tricia (The Guilford Press, 2016)
"Addressing practical issues rarely covered in methods texts, this user-friendly, jargon-free book helps students and beginning researchers plan infant and child development studies and get them done. The author provides step-by-step guidance for getting involved in a developmental laboratory and crafting effective research questions and proposals. Tips on recruiting study participants cover access issues--such as how to overcome language and cultural barriers--and include helpful sample scripts. The book offers time management strategies, pointers for organizing and communicating data, and a road map of the journal publication process, complete with an annotated sample article. Numerous concrete examples, checklists, worksheets, and exercises are featured. Reproducible forms can be downloaded and printed in a convenient 8 1/2" x 11" size. Pedagogical Features: *Chapter subheadings written as questions to help students quickly find the answers they need. *Boxed key tips and checklists for managing each phase of a study. *Exercises that build core research skills. *Annotated sample journal article with commentary on the writing and publication process"--Provided by publisher.